Intervensi Penyuluhan Gizi Seimbang dengan Media Video terhadap Perubahan Asupan Zat Gizi Remaja Putri - Icha Dian Nurcahyani (Sarana Ilmu Indonesia (salnesia), 2020)
Women play an important role as determinants of the quality of future generations, therefore it is important to ensure that women's nutritional status does not have problems as early as possible. The risk of chronic lack of energy (KEK) in pregnant women because the mother has experienced KEK in adolescence, one of which is caused by the intake of nutrients that are not adequate. The purpose of this study was to find out the effect of nutritional counseling interventions balanced with video media on changes in the nutritional intake of Adolescence Girls of SMPN 1 Turikale Kab. Maros This research used experimental pre-design with one group of pre-post test design. Variable research on nutritional intake was measured before and after being given balanced nutrition counseling with video media. Data collection used online questionnaires and research subjects numbered 40 people, female gender. Statistical analysis used Kolmogorov and Paired t-test. The results showed that there was no difference in energy intake (p= 0.412), carbohydrate intake (p=0.052), and protein intake (p=0.559) before and after balanced nutrition counseling, but there were differences in fat intake (p=0.008) and iron intake (p=0.007) before and after balanced nutrition counseling. It can be concluded that there was a significant change between fat intake and iron intake after receiving counseling.